Developmental Counselling and Therapy: Integrating Constructivism and Cognitive Development in Counselling Settings - Daniels, Thomas G. (Canadian Journal of Counselling and Psychotherapy, 2007)
Developmental Counselling and Therapy (DCT) is a model of helping which is based on Piagetian and constructivist concepts. Client functioning is understood in terms of four levels of cognitive developmental functioning which parallel the levels of cognitive development described by Piaget. The counselling process facilitates both intra- and inter-level development. The point of departure in DCT is to start with the clients' predominant cognitive developmental level and then to match counseling strategies which promote client development. Client growth occurs as the client develops more effective constructs at her/his predominant cognitive-developmental level and is further challenged to function at other less utilized cognitive developmental levels. Early research evidence offers support for DCT.